Cultural Identity and Recognition: Ethnic Minority Rights in Bangladesh through Kymlicka’s Multiculturalism - Aktar, Solnara (The Jahangirnagar Review Part-C, 2025)
This paper explores the multifaceted challenges faced by ethnic minorities in Bangladesh, emphasizing their distinct linguistic, cultural, and social identities. These communities experience persistent ethnocultural injustice, including discrimination by the state, internal community conflicts, and violations of fundamental rights. Indigenous women, in particular, suffer from layered oppression due to their gender and ethnic identity, facing both patriarchal violence within their communities and systemic marginalization outside. Based on Kymlicka’s Multiculturalism, this study argues that existing human rights frameworks are inadequate to protect ethnic minority peoples in Bangladesh, especially regarding internal displacement, language policies, and political representation. Moreover, this paper emphasizes implementing “Citizenship Education” in Bangladesh to foster respect for cultural diversity and promote democratic values. It further recommends legal reforms, such as recognizing customary land rights, ratifying international conventions, and fully implementing the 1997 Chittagong Hill Tracts Accord. Additionally, the paper highlights the urgent need for inclusive national policies that ensure equitable access to education, healthcare, and political participation for ethnic minorities, particularly women. It concludes by identifying critical areas of ethnic minorities for further research, including community-specific challenges, Marginalization of women based on race, class, and gender identity, and the role of religious institutions in shaping identities.